Systolic anterior motion of the mitral valve—the mechanism of postural hypotension following left intrapericardial pneumonectomy - Lasala, Javier D.; Tsai, January; Rodriguez-Restrepo, Andrea; Atay, Scott Michael; Sepesi, Boris (Journal of Thoracic Disease, 2017)
Systolic anterior motion (SAM) is defined as displacement of the distal portion of the anterior leaflet of the mitral valve toward the left ventricular outflow tract obstruction. SAM can occur in patients without hypertrophic cardiomyopathy (HOCM) and is a well-recognized cause for unexplained sudden hypotension in perioperative settings. We present a case of persistent orthostatic hypotension caused by SAM following left intrapericardial pneumonectomy and mediastinal lymph node dissection for squamous cell carcinoma of the lung invading intrapericardial portion of the inferior pulmonary vein. Diagnosis of SAM was possible with the use of transesophageal echocardiography (TEE).